TDM in psychiatry and neurology: A comprehensive summary of the consensus guidelines for therapeutic drug monitoring in neuropsychopharmacology, update 2017; a tool for clinicians*. (3rd April 2018) - Schoretsanitis, Georgios; Paulzen, Michael; Unterecker, Stefan; Schwarz, Markus; Conca, Andreas; Zernig, Gerald; Gründer, Gerhard; Haen, Ekkerhard; Baumann, Pierre; Bergemann, Niels; Clement, Hans Willi; Domschke, Katharina; et al.
Abstract: Objectives: Therapeutic drug monitoring (TDM) combines the quantification of drug concentrations in blood, pharmacological interpretation and treatment guidance. TDM introduces a precision medicine tool in times of increasing awareness of the need for personalized treatment. In neurology and psychiatry, TDM can guide pharmacotherapy for patient subgroups such as children, adolescents, pregnant women, elderly patients, patients with intellectual disabilities, patients with substance use disorders, individuals with pharmacokinetic peculiarities and forensic patients. Clear indications for TDM include lack of clinical response in the therapeutic dose range, assessment of drug adherence, tolerability issues and drug–drug interactions. Methods: Based upon existing literature, recommended therapeutic reference ranges, laboratory alert levels, and levels of recommendation to use TDM for dosage optimization without specific indications, conversion factors, factors for calculation of dose-related drug concentrations and metabolite-to-parent ratios were calculated. Results: This summary of the updated consensus guidelines by the TDM task force of the Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie offers the practical and theoretical knowledge for the integration of TDM as part of pharmacotherapy with neuropsychiatric agents into clinical routine. Conclusions: The present guidelines for TDM application for neuropsychiatric agents aim to assist clinicians in enhancing safety and efficacy of treatment.